Multipurpose Fluorescent Nanocarriers: Environmental Behavior, Toxicity and Internalization on Marine Microalgae - Campos, Bruno G. [UNESP]; Kaczerewska, Olga; Oliveira, Jacinta M. M.; Figueiredo, Joana; Maia, Frederico; Tedim, João; Sousa, Isabel; Abessa, Denis M. S. [UNESP]; Loureiro, Susana; Martins, Roberto (Wiley, 2025)
Engineered nanomaterials (ENMs), such as silica mesoporous nanocapsules (SiNC), have emerged as a powerful tool for the controlled delivery and release of active compounds in various fields. However, the environmental impact of SiNC on marine biota, particularly when they enter the marine environment through wastewater effluents or direct release from maritime coatings, remains poorly understood. Studying their effects is thus crucial for environmental and human health protection, the development of safe-by-design ENMs, and informed policy-making. This study aims to assess the ecotoxicological effects and internalization of industrially-relevant SiNC in marine phytoplankton, namely on the microalgae Tetraselmis chuii, Nannochloropsis gaditana, and Isochrysis galbana, and diatoms Phaeodactylum tricornutum, and Chaetoceros calcitrans. For this purpose, a fluorescent nanocarrier (SiNC-UMB) is developed by labeling the SiNC with the fluorescent natural dye umbelliferone (UMB). UV–vis and fluorescence spectroscopic analyses confirmed the successful loading of UMB into SiNC. Phytoplankton can internalize these ENMs, even at low concentrations, although adsorption to the cell wall can also occur. This confirms the internal exposure and growth inhibition observed in the microalgae. These findings highlight the potential of using SiNC-UMB as a valuable tool for tracking their uptake and assessing their effects on marine biota and beyond.
Keywords: fluorescent labeling; nanomaterials; natural dyes; silica mesoporous nanocapsules; umbelliferone